Fostering diversity a study on racial diversity in Swope Park - Jagels, Emily (Kansas State University, 2017)
Race tension has increased in America as contemporary issues occur. Riots and protests are becoming common once again. The research presented shows how park space can help foster diversity and in turn improve race relations in the Kansas City area. The study shows how communities in Kansas City became segregated based on historical laws, regulations, and common day practices that reinforced racial boundaries between communities. Many still feel racial tension stemming from historical events today. A focus on integration within communities can be the first step in creating harmony and healing people who have felt these negative impacts on their lives. A literature review, including historical documents from Kansas City and similarly structured racially divided cities, such as St. Louis, Missouri, Detroit, Michigan, and Chicago, Illinois, were analyzed. Research lead to focusing in on Swope Park and the surrounding community. Swope Park has a complex history of segregation and is located near Troost Avenue, which is one of the greatest racial divide lines in the United States. To the west of Troost Avenue the race is predominantly white while to the east is composed mostly of African Americans. On site observational surveys and short interviews with users of Swope Park were conducted to determine current use, users, and park qualities. Qualtrics Surveys were released to community organization to survey a larger group of people, some of whom might not currently use the park. The analyzed information gathered helped shape an innovative design suggestion and strategy to promote diversity and integration at Swope Park. This research can help shape a diverse future of racially integrated communities in the Kansas City area to promote economic stimuli, break down racial stigmas, and increase education, understanding, and celebration of diverse racial backgrounds.
Keywords: Park; Public spaceRacial diversity